Performance analysis of a downdraft and fluidized bed biomass gasification using thermodynamic equilibrium model - Gan, Gek Hian (2015)
Gasification is a process of producing fuel gas or synthesis gas from biomass using gasifier. The gas produced through this process particularly hydrogen will be utilized further as an input for power generation in order to produce energy. Due to the environmental concern and sustainability issues, energy from biomass has become one of the most promising renewable sources of energy. Current research points to improve the gasifier performance in order to elevate more economical product from the gasifier. For this purpose, the thermodynamic equilibrium model can be employed to predict the gas composition and to optimize important gasifier parameters for various kinds of gasifiers as well as utilizing various types of biomasses. In this work, the biomasses consisting of wood, rice husk, saw dust and empty fruit brunch are selected considering their low cost and availabilities as an abundant resource in Malaysia. These biomass sources are then served as the inputs for downdraft and fluidized bed gasifier for producing the hydrogen gas and through this study, the performance analysis in terms of the optimal parameters and gas output composition are then carried out. Here the air is used as an input reactant for downdraft gasifier and the fluidized bed gasifier is employing steam for the gasification process. In this work, the model validation is carried out first where the gas composition data obtained from thermodynamic equilibrium model show good agreement with experimental result from Zainal et al. (2001) for downdraft gasifier employing wood and Karmakar and Datta (2011) for fluidized bed gasifier using rice husk. Afterwards the performance analysis is performed to investigate the optimum parameters for downdraft and fluidized bed gasifiers. Based on this analysis, the optimum parameters obtained are at temperature 770°C with moisture content of 0.2 and steam biomass ratio 1.32, the hydrogen gas produced from wood, rice husk, sawdust and empty fruit bunch in downdraft gasifier is 16.38%, 17.02%, 16.30% and 50.12% respectively, while in the fluidized bed gasifier is 38.75%, 50.00%, 73.30% and 71.77% respectively. The result of the performance analysis shows that the fluidized bed gasifier is more efficient than downdraft gasifier in term of hydrogen gas production.